Association Between Interleukin 16 Gene Polymorphisms (rs1131445, rs4072111) and Late Onset of Alzheimer's Disease in Iranian Patients - Nazanin Esmaeili Anvar; Niloofar Bazazzadegan; Mina Ohadi; Kourosh Kamali; Hamidreza Khorram Khorshid (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Alzheimer’s disease is the most common kind of dementia in the old age, and its incidence increases with age. Previous studies have shown that cytokines are proteins that play an important role in inflammation, and their level changes in inflammatory diseases. Since Alzheimer’s disease is an inflammatory disease, cytokines may influence the occurrence of this disease. IL16 is a cytokine whose role has been proved in many inflammatory diseases. This gene is one of the coding genes of cytokines of the inflammatory process. It may be responsible for inflammatory pathology seen around old age plaques in Alzheimer’s disease. It can also associate with the pathology of Alzheimer’s disease. Therefore, the aim of this study was to investigate the effects of 2 polymorphisms of gene IL16 (rs1131445 and rs4072111) on the risk of patients diagnosed with Alzheimer’s disease in the Iranian population. Methods & Materials: In this study, the intervention group consisted of 144 individuals who were diagnosed with Alzheimer’s disease by psychologists based on a clinical test (DSM-IV), and the control group included 173 healthy individuals with no psychological disorders. DNA was extracted by salting out technique. The PCR response was conducted (for replicating the mentioned pieces) for any polymorphism in optimized conditions by using designed primers. The product of PCR was first checked for the confirmation of accurate function of PCR using polyacrylamide gel electrophoresis (PAGE). Next, the PCR product was dissected by restriction fragment length polymorphism (RFLP) method with intended confining enzyme, and then the genotype of the samples was determined by PAGE. Individual genotypes were determined using the PCR-RFLP method. Statistical analyses were done using OpenEpi 2.3.1 and SPSS 11.5. Results: The study of allelic analysis between the control and intervention groups by considering the confidence interval (CI=90%) and significant level (0.05) for rs1131445 showed that the C allele had no significant association with Alzheimer’s disease (P=0.656). The TC genotype did not show any significant difference with TT genotype (P=0.614). However, the study of allelic analysis for rs4072111 polymorphism between 2 groups showed that the relationship of T allele with the disease is significant, and this allele has a protective role in creating the disease (P=0.008). In addition, TC genotype as a protective status showed a significant association with Alzheimer’s disease (P=0.007). Conclusion: The existence of polymorphism in some genes of the inflammatory pathway could make people susceptible to Alzheimer’s disease. The genetic changes in DNA sequence of gene IL16 could result in changes in cytokine product or its function. The association between rs4072111 and Alzheimer’s disease supports the presumptions and shows a probable role of this polymorphism in Alzheimer disease. Besides, the association between rs1131445 and Alzheimer disease cannot be proven due to the small number of samples (Power: 8.23%).